‘A box the shape of me’: the challenge of developing and evaluating patient-centred outcomes for use in eczema clinical trials - Howells, Laura Mary (2020)
Background: Eczema is a chronic, itchy skin condition with onset typically in early childhood. Clinical trials compare health-related outcomes between two or more groups receiving different interventions. The Harmonising Outcome Measures in Eczema (HOME) initiative is an international collaboration working together to develop a core outcome set of outcome measures to be included in all eczema clinical trials to improve the comparability of outcome measures across trials.